Antibiotics The Perfect Storm - Shlaes, David M. (Springer Netherlands : Imprint: Springer, 2010)
Antibiotics are truly miracle drugs. As a class, they are one of the only ones that actually cure disease as opposed to most drugs that only help relieve symptoms or control disease. Because bacteria that cause serious disease in humans are becoming more and more resistant to the antibiotics we have today, and because they will ultimately become resistant to any antibiotic that we use for treatment or for anything else (like crops, animals, etc.), we need a steady supply of new antibiotics active against the resistant bacteria that arise. But the antibiotics marketplace is no longer attractive for large pharmaceutical companies, the costs of development are skyrocketing because of ever more stringent requirements by the regulatory agencies and finding new antibiotics active against resistant strains is getting harder and harder. These forces are all combining to deny us these miracle drugs when we need them the most. I provide a number of possible paths to shelter from this perfect storm.